Role of Nanobacteria in the Development of Nephrolithiasis: A Systematic Study - Alemzadeh, Effat; Farkhondeh, Tahereh; Aschner, Michael; Pourbagher-Shahri, Ali M.; Alemzadeh, Esmat; Salehinia, Hamid; Ranjbar Garmroodi, Bardia Zamani; Bideh, Milad; Abedi, Farshid; Samarghandian, Saeed (Current Nanoscience, 2023)
Background & Aims: Nanobacteria are unconventional agents that are 100-fold smaller than common bacteria. It has been hypothesized that nanobacteria are responsible for kidney stone formation. This systematic review was designed to address this question related to the role of nanobacteria in the development of nephrolithiasis. Methods: Keywords related to nanobacteria and nephrolithiasis on MeSH were identified and searched in PubMed, Scopus, Google Scholar, and Web of Science until Oct 2021. The full text of identified papers was obtained and assessed based on exclusion and inclusion criteria. The reviews is based on articles that have focused on the role of nanobacteria in nephrolithiasis. Result: A total of 17 studies were identified based on the inclusion criteria; however, nine studies qualified for this systematic review. The findings of the 9 articles indicated the role of nanobacteria in nephrolithiasis. After assessing the quality of the study, 7 papers were included in this systematic study. Conclusion: Regarding the limitation of the short number of evidence to recognize how nanobacteria cause kidney stones, nevertheless it is obvious that high concentrations of nanobacteria are directly related to initiating crystal nucleation in the kidney and lead to nephrolithiasis; some variables like physiochemical factors, gender and so on could certainly affect crystallization in kidneys. Also, therapeutic decisions for these issues are limited to antibiotics. Our findings, by focusing on the impact of nanobacteria on kidneys, bring a new overview to the study of the factors related to them.
Keywords: antibiotics